(untitled) (REMUNOM, 2024)
Generalized Anxiety Disorder (GAD) is a highly prevalent disorder in Brazil with a significant impact on public health. It is characterized by excessive and persistent worries, accompanied by physical and cognitive symptoms that compromise the individual’s functionality. Objective: This article aimed to characterize GAD according to the criteria of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, Text Revision (DSM-5-TR) and the International Statistical Classification of Diseases and Related Health Problems, 11th edition (ICD-11). In addition, we sought to describe CBT techniques for the treatment of GAD. Methods: This is a narrative review of the literature. Results: CBT offers effective techniques for the treatment of GAD, such as psychoeducation, cognitive restructuring, problem-solving, Socratic questioning, sleep hygiene, muscle relaxation, diaphragmatic breathing, and mindfulness. Conclusion: CBT is effective in the treatment of GAD, providing symptom reduction and improving the quality of life of patients.